An analysis on the research orientations in healthcare simulation modeling - Chen, J.; Chun, D.; Oliveira, M. D.; Fernandes, A. (2019 Spring Simulation Conference (SpringSim), 2019)
Research orientation is about for whom and by whom the research is conceptualized and conducted. A clear understanding of this often-overlooked concept is crucial for the healthcare modeling community, which is searching for better stakeholder engagement, value demonstration and quality assessment. To review and categorize this concept for modelers and evaluators, we used the Framework Method to examine 35 purposively sampled studies of agent-based and discrete-event simulation modeling in healthcare operation and policy. Four research orientations emerged in the sampled studies, ranging from academic, unilateral passive stakeholder, unilateral active stakeholder, and multilateral stakeholders. From one orientation to the next, studies engage more stakeholders in more research steps and entail distinct requirements for quality assessment. Our analysis highlights the complexity of healthcare for which the best approach to engage stakeholders, demonstrate value and assess quality depends upon the research orientation.